Determining Prognosis in Neonates with Transient Tachypnea by Using Retraction Scores (Annals of Medical Research, 2021)
Aim: The aim of this study is to evaluate the accuracy of physical and laboratory findings to determine the length of hospital stay and oxygen requirement in patients diagnosed with transient tachypnea of the newborn.
Keywords: Blood Gas Analysis; Neonatology; Neonatal Intensive Care; Respiratory Insufficiency; Transient Tachypnea of The Newborn.